2011
DOI: 10.1093/jscr/2011.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Leukaemic infiltration of gall bladder – unusual presentation of occult chronic lymphocytic leukaemia

Abstract: Extramedullary involvement in early stage chronic lymphocytic leukaemia (CLL) is rare. We report the first case of an incidental finding of gall bladder infiltration in a patient who underwent a cholecystectomy for gallstone pancreatitis with no preceding history of CLL. This case reiterates the importance of subjecting even routine cholecystectomy specimens for histopathology examination in the context of this unusual presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Secondary (5): B-cell lymphoma (4 cases), CHL (1 case). 13 Rao et al [ 13 ] 2011 Gallbladder 1 CLL 14 Esfahani et al [ 14 ] 2011 Liver 1 CLL 15 Ozawa et al [ 8 ] 2012 Gallbladder 1 B-LL 16 Psarras et al [ 5 ] 2014 Gallbladder 1 B-LL (primary) 17 Azin et al [ 19 ] 2014 Gallbladder 1 AML 18 Mitropoulos et al [ 20 ] 2015 Gallbladder 1 T-LL (primary) 19 Sayyed et al [ 9 ] 2018 Liver 1 ALL 20 Jafroodifar et al [ 15 ] 2021 Gallbladder 1 CLL 21 Present case report, Rahim et al 2022 Gallbladder 1 B-LL ALL acute lymphoblastic leukemia/lymphoma, B-LL B-lymphoblastic leukemia/lymphoma, T-LL T-lymphoblastic leukemia/lymphoma, CLL chronic lymphocytic leukemia, AML acute myeloid leukemia, FL follicular lymphoma, DLBCL diffuse large B-cell lymphoma, CHL classic Hodgkin lymphoma, MCL Mantle cell lymphoma …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary (5): B-cell lymphoma (4 cases), CHL (1 case). 13 Rao et al [ 13 ] 2011 Gallbladder 1 CLL 14 Esfahani et al [ 14 ] 2011 Liver 1 CLL 15 Ozawa et al [ 8 ] 2012 Gallbladder 1 B-LL 16 Psarras et al [ 5 ] 2014 Gallbladder 1 B-LL (primary) 17 Azin et al [ 19 ] 2014 Gallbladder 1 AML 18 Mitropoulos et al [ 20 ] 2015 Gallbladder 1 T-LL (primary) 19 Sayyed et al [ 9 ] 2018 Liver 1 ALL 20 Jafroodifar et al [ 15 ] 2021 Gallbladder 1 CLL 21 Present case report, Rahim et al 2022 Gallbladder 1 B-LL ALL acute lymphoblastic leukemia/lymphoma, B-LL B-lymphoblastic leukemia/lymphoma, T-LL T-lymphoblastic leukemia/lymphoma, CLL chronic lymphocytic leukemia, AML acute myeloid leukemia, FL follicular lymphoma, DLBCL diffuse large B-cell lymphoma, CHL classic Hodgkin lymphoma, MCL Mantle cell lymphoma …”
Section: Discussionmentioning
confidence: 99%
“…Most cases of leukemic infiltration of gallbladder present with clinicopathological features closely resembling acute and/or chronic cholecystitis [ 6 , 11 13 , 16 , 17 ]. Azin et al reported a patient with known AML who received chemotherapy and achieved a morphological free state.…”
Section: Discussionmentioning
confidence: 99%
“…Ratterman et al, in the systematic analysis of cases reported between 1975 and 2012, states that the central nervous system (CNS) and skin were the most commonly identified sites of spread, with some evidence that prognosis could be related to the location of involvement [6]. Less commonly, the involvement of the prostate, gallbladder, pituitary, thyroid, orbit, nasal mucosa has been reported [5,7]. Rarely, endocardial deposits can be seen with intracavitary growth and even rarer tumor infiltration of heart valves [8].…”
Section: Discussionmentioning
confidence: 99%
“…T-cell neoplasms reported as part of composite lymphoma (or possible transformation) with CLL/SLL have been of cytotoxic CD8 + T cell immunophenotype and we are unaware of any reports of cases similar to the case we report. Incidental CLL/SLL found in lymph nodes evaluated for other reasons is not an uncommon event [4750]; however, the incidental finding of T-PLL is rare [4]. The presence of CLL/SLL in the dissected lymph node, though in a rare follicular pattern [51], in conjunction with a CLL/SLL clone in the peripheral blood, led to inadvertent failure to diagnose the concurrent T-PLL in the same lymph node.…”
Section: Discussionmentioning
confidence: 99%